Analysis of Real Estate Market Development Indicators in the Republic of Uzbekistan - Fayziyeva Gulnoza Abdurumanovna (Genius Journals, 2023)
The analysis of indicators of development of the residential real estate market in the Republic of Uzbekistan, the analysis of appraisal organizations and realtor organizations is presented.
Keywords: Real estate; valuation; appraisal organizations; apartment